The effectivity of Cone Beam Computed Tomography (CBCT) in dentigerous cyst management: a literature review - Anak Agung Gde Dananjaya Agung; Ni Kadek Sintya Anggreni (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2022)
Objectives: This review aims to understand the effectiveness of Cone Beam Computed Tomography (CBCT) in the management of dentigerous cysts by looking at the advantages and disadvantages based on the quality of the resulting radiographic images. Review: Based on the literature review that has been carried out on 10 journals were eliminated from 22 journals that had the criteria according to the topic but there was a duplication in the identification results of the initial 50 journals from Pubmed, Google Scholar, ScienceDirect, and EuropePMC, with a range of 2012-2022 using the Boolean Operator Strategy with inclusion criteria developed from PICOS framework, it was found that the CBCT radiographic method is the most widely used method in the management of dentigerous cysts because of the predominance of advantages over disadvantages. This radiographic method is able to produce three-dimensional radiographic images without overlapping structures, distortions, and amplifications at a low cost, although it has weaknesses. Conclusion: CBCT 3D may assess dentigerous cyst lesions effectively by taking into account several considerations and the accuracy of the SOP in its use. This radiography method can provide clear radiographic images without structural overlap, distortion, and amplification at a low cost to confirm the diagnosis and determine the appropriate treatment plan despite the drawbacks as a new result of development technologies in dental radiography.